(untitled) (Revista Internacional de Formação de Professores, 2023)
This writing aims to investigate the constitution of the identity of teachers of Specialized Educational Assistance, starting from the experiences, memories and conceptions produced before and during teaching. The study, of a qualitative nature, carried out an autobiographical research with a teacher who works in the Municipal Education Network of Caucaia - Ceará.The results demonstrate that the identity teacher researched is intimately related to the process of professional socialization, as the way in which she sees herself and is seen was predominantly the result of her social and professional experiences.